Bovine Pericardial Graft for Second-Trimester Cesarean Scar Dehiscence. Issue 2 (February 2019) - Stephens, Angela; Patel, Khilen; Davis, Janet; Ghamande, Sharad
Abstract : BACKGROUND: Cesarean scar dehiscence is rare in pregnancy. When it occurs late in pregnancy, management typically involves delivery of the fetus with concurrent uterine repair. However, consensus regarding management earlier in gestation is lacking. CASE: A 30-year-old African American woman, gravida 5 para 2113, presented with cesarean scar dehiscence confirmed by magnetic resonance imaging at 20 weeks of gestation. She desired pregnancy continuation and underwent repair of the dehiscence at 23 weeks of gestation using bovine pericardial graft. She subsequently underwent cesarean delivery at 35 weeks of a healthy neonate after going into preterm labor. CONCLUSION: Bovine pericardial graft is a viable option for repair of cesarean scar dehiscence in the second trimester. Abstract : A bovine pericardial graft can be used to successfully repair uterine scar dehiscence in the second trimester.